EXAMINING THE PREVALENCE OF THROMBOPHILIA IN WOMEN WITH FETAL LOSS - Mandić, Danijela M (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: In addition to antiphospholipid syndrome (APS), inherited thrombophilia is one of the most important hematologic disorders that can lead to pregnancy complications such as fetal loss, intrauterine growth restriction (IUGR), preeclampsia, and fetal death. The frequency of spontaneous abortions is up to 20% of all clinically recognized pregnancies.Objective: The aim of this study was to determine the frequency of inherited thrombophilia in women with fetal loss, analyze the gestational period and age at which fetal loss occurred, and assess the frequency of successful pregnancies after prophylactic use of low molecular weight heparin (LMWH).Material and methods: The study was designed as a 30-month retrospective observational study at the Clinic for Gynecology and Obstetrics of the University Clinical Center of the Republic of Srpska, involving 69 patients with one or more fetal losses in the second and third trimesters of pregnancy, or two or more repeated fetal losses in the first trimester of pregnancy. All patients underwent tests to detect the presence of thrombophilia.Results: The average age of the patients was 30.7 years, and they had a total of 167 unsuccessful pregnancies. Thrombophilia was proven in a total of 40 patients (58%). The results showed that combined thrombophilia, including polymorphisms, occurred most frequently – 47.5% (n=19). In the group of patients with inherited thrombophilia, low molecular weight heparin (LMWH) was administered to 22 patients and it resulted in a successful pregnancy outcome in 19 patients.Conclusion: Based on the conducted research, it can be concluded that combined thrombophilia, including combined polymorphisms MTHFR and PAI-1, carry a significantly higher risk of pregnancy loss in patients of all age groups. Age over 35 years is a risk factor for higher frequency of spontaneous abortions irrespective of the type of inherited thrombophilia. The use of LMWH significantly improves pregnancy outcomes in patients with inherited thrombophilia and previous pregnancy losses.
Keywords: trombophillia; fetal loss; low molecular weight heparin